Sistematik Literatur Review: Persepsi Mahasiswa Indonesia pada Pembelajaran Elektronik Era Pandemi Covid-19 - Siti Nur Indah Rofiqoh; Raditya Sukmana; Ririn Tri Ratnasari; Muhammad Nafik HR; Zulfa Mufidah; Anik Rufaidah; Muhammad Ala’uddin (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This article aims to measure the student’s perception about electronic learning in Covid-19 era hat causing apprehension, deep changes in education policy. This article used the literature systemic review as the approaches. Searching for literature article, researcher was primary collected from Google scholar and Scopus during 2020 to 2021. The research gap highlighted by VOS-viewer software. Matching articles consist of 2 qualitative literature studies with thematic analysis, 1 article used mixed method analysis study, 1 modified pre and post-test experimental control group design paper, and 1 descriptive research article study through the google form link study. The review concluded that electronic learning should have been done by various kinds of supporting application platforms, various learning methods and also various self-motivations. The supporting application platforms such as Zoom, Google Classroom, university web, WhatsApp group and virtual libraries. The supporting learning methods such as e-conferences, e-games, e-writing contests and e-libraries action. The several self-motivations are self-developed and maintained continuously, independent learning, self-awareness, and self-learning achievement, and also initiative blended learning. Abstrak. E-learning atau pembelajaran dalam jaringan harus dilakukan oleh hampir seluruh dosen di Indonesia pada saat Pandemi Covid 19. Meskipun jarak jauh, dosen harus menjamin kualitas Pendidikan sesuai kebutuhan para pemangku kepentingan. Menggunakan berbagai aplikasi pendukung pendidikan tinggi berbasis internet, beberapa artikel telah ditulis guna mengukur persepsi ketercapaian e-learning. Metode penelitian ditetepakan menggunakan literatur sistematik review bersumber artikel pada Google Scholar dan Sopus yang diolah menggunakan software VOS-viewer untuk menetapkan gap penelitian. Lima artikel data penelitian terdiri dari 2 artikel kualitatif analisis tematik, 1 artikel metode penelitian campuran, 1 artikel eksperimen dan 1 artikel deskriptif menggunakan google form sebagai link kuisioner. Hasil analisis menunjukkan kesimpulan bahwa ketercapaian e-learning didukung oleh ketepatan penggunaan aplikasi, ketepatan pemilihan metode pembelajaran dan penanaman motivasi kemandirian belajar. Penggunaan aplikasi yang tepat, seperti Zoom, Google Classroom, Wesite pembelajaran kampus, grup WhatsApp dan perpustakaan online. Metode pembelajaran pendukung e-learning seperti presentasi online, game online, tugas menulis online dan akses perpustakaan online. Adapun penanaman kemandirian belajar dapat diwujudkan melalui kepemilikan jiwa pengembangan diri, konsistensi diri, keberlanjutan, kemandirian, kesadaran, pencapaian dan inisiatif belajar.